1964
DOI: 10.1007/bf01418533
|View full text |Cite
|
Sign up to set email alerts
|

Versuch einer axiomatischen Grundlegung der Quantenmechanik und allgemeinerer physikalischer Theorien

Abstract: Es wird versucbt, durch Einfiihrung gewisser axiomatisctier Annahmen iiber die Erzeugung yon Makroeffekten dutch Mikroobjekte zu einer allgemeinen Grundstruktur physikaliseher Theorien zu kommen. Eine Ubersicht tiber alle mathematischen M6glichkeiten, die das aufgestellte Axiomensystem erffillen, ist noch nicht gelungen; es zeigen sich aber schon die wesentlichen Eigenschaften des quanten, mechanischen Aussagekalktils. Einfiihrung in die ProblemstellungW~ihrend der historischen Entwicklung wurde die Quantenmec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 0 publications
1
82
0
Order By: Relevance
“…This reduces to the joint measurability condition η ≤ η opt for Alice's local unsharp measurements, as one can identify a striking agreement between the degree of incompatibility η opt (given by (12) and listed in Table. II)) and the upper bound f (N ) (given in (36)) of the finite setting linear steering inequality (35). This is a clear example of the intrinsic connection (established in Refs.…”
Section: Joint Measurability Condition From Linear Steering Inequamentioning
confidence: 73%
See 2 more Smart Citations
“…This reduces to the joint measurability condition η ≤ η opt for Alice's local unsharp measurements, as one can identify a striking agreement between the degree of incompatibility η opt (given by (12) and listed in Table. II)) and the upper bound f (N ) (given in (36)) of the finite setting linear steering inequality (35). This is a clear example of the intrinsic connection (established in Refs.…”
Section: Joint Measurability Condition From Linear Steering Inequamentioning
confidence: 73%
“…However, non-commuting observables are declared as incompatible under the regime of PV measurements. Introduction of POVMs in 1960's by Ludwig [35] and subsequent investigations on their applicability [36], led to a mathematically rigorous generalization of measurement theory. It is the notion of compatibility (the notion of compatibility of a set of POVMs will be defined in the following) -rather than commutativity -which gains importance so as to recognize if a given set of POVMs are jointly measurable or not [37].…”
Section: Joint Measurability Of Povmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the later development of quantum theory, several authors suggested the generalized representation of observables as positive operator measures [9][10][11]). This concept advanced the mathematical coherence and conceptual clarity at first of quantum mechanics and then of quantum field theory.…”
Section: The Ubiquity Of Natural Operatorsmentioning
confidence: 99%
“…More specifically, joint measurability or compatibility of observables is entirely linked with their commutativity, if sharp PV measurements are employed. However, with the introduction of generalized measurements -formulated in terms of positive operator valued measures (POVMs) -it has been possible to refine the notion of joint measurability of non-commuting observables [1][2][3][4] . While sharp values for non-commuting observables can not be assigned jointly via their PV measurements, their unsharp joint values could be perceived when compatible POVMs are employed.…”
Section: Introductionmentioning
confidence: 99%